Theory of mind skills and peer relationships in children’s adjustment to preschool - Ünlüer, Esra (Frontiers in Psychology, 2024)
School adjustment affects children’s future lives in many ways. This study examined the relationship between ToM skills, peer relationships, and school adjustment. Specifically, this study determined whether preschool children’s school adjustment could be significantly predicted by theory of mind (ToM) skills and peer relationships. A total of 164 children aged 4 (34.5%), and 5 (38%) years of preschool attendance participated in the study. According to the research, children’s age, theory of mind, peer relations, and school adjustment are closely related. It was also found that the theory of mind significantly predicted school adjustment (school liking/avoidance) and that prosocial and aggressive behavior predicted school liking.